Method for testing modification performance of relic soil of shopping mall under high water content
By adding sodium methyl silicate to the soil in the mall site and using the "step progressive" repair method, a silicone resin film was formed, which solved the problem of reduced soil stability under high moisture content, and achieved soil mechanical properties and water Significant improvement in rational performance.
Patent Information
- Application Number
- CN202411645403.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2024-11-14
- Filing Date
- 2024-11-18
- Publication Date
- 2025-02-18
AI Technical Summary
The prior art is difficult to effectively improve the mechanical properties and water performance of the soil in the mall site under high moisture content, resulting in a decrease in soil stability and prone to cracks and falls, which in turn aggravates the degradation and disappearance of the site.
The site soil is improved by adding sodium methyl silicate liquid and using the "step progressive" repair method, a network-shaped silicone resin film is formed, wrapped on the surface of the soil structure, achieving the "anti-capillary effect" and forming a hydrophobic layer. Enhance the compactness and shear strength of the soil.
Effectively improve the mechanical properties and water properties of the site soil, enhance the shear strength and disintegration resistance of the soil, extend the penetration depth of the restoration materials, solve the problem of the limitation of the penetration depth of liquid materials, and significantly improve the The stability of the site soil.
Smart Images

Figure CN119470850A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of ruins restoration, in particular to a test method for soil modification performance of a Shang city ruins under high water content. Background Art
[0002] The Zhengzhou Shang City Ruins are located in the old city of Zhengzhou, in the lower reaches of the Yellow River, with abundant surface water resources. In the "July 20" incident in Zhengzhou in 2021, the Shang City Ruins were severely damaged by rain erosion. Water is the main channel for salt migration in the soil. Under the action of capillary action, groundwater will cause soluble salts to diffuse and migrate in the soil of the site. The soluble salts migrate from the surface of the soil to the interior of the soil. Under the action of evaporation, the soil surface dries rapidly, changing the surface tension between soil particles, and causing varying degrees of shrinkage and salt swelling. The agglomeration effect of soluble salts will increase the porosity, leading to heterogeneous shrinkage between the crust layer and the loose layer. Repeated cycles will produce a large number of cracks inside the soil, causing the soil particles to disperse and fall off, and the soil stability will be reduced. Affected by external environment such as wind, rain, and temperature and the soil's own characteristics, the soil has evolved from peeling to falling off. The reciprocating and progressive destruction of the site has aggravated the degradation and disappearance of the earthen site. In recent years, the addition of admixtures is often used to modify the site soil in the restoration of earthen sites.
[0003] The existing restoration of earthen sites with the addition of external admixtures has the following defects: First, organic modified materials such as acrylic epoxy resin have a good restoration and reinforcement effect on earthen sites, and have the characteristics of water resistance, corrosion resistance, and high strength, but they are prone to yellowing over time, lack durability, have poor aging resistance, and the aging products are incompatible with soil; Second, the chemical composition of inorganic materials is similar to that of soil, and they are resistant to aging, but they have large shrinkage, poor water resistance, and the reinforcement effect is not obvious; Third, inorganic-organic composite modified materials combine the aging resistance and air permeability of inorganic materials with the flexibility and hydrophobicity of organic materials. After reinforcement, the appearance is not affected, but the aging resistance, water resistance and air permeability are poor; Fourth, the current protection of earthen sites mainly adopts the method of surface spraying liquid for restoration. Affected by the soil penetration resistance, surface temperature stress and internal hot and humid gases, the penetration depth of earthen sites is relatively shallow. Summary of the invention
[0004] The purpose of the present invention is to provide a test method for the soil modification performance of Shangcheng ruins under high moisture content, so as to solve the problems raised in the above-mentioned background technology.
[0005] To achieve the above object, the present invention provides the following technical scheme: a test method for the modified performance of Shangcheng ruins soil under high water content, comprising step 1, soil sample preparation; step 2, direct shear test; step 3, disintegration test; step 4, scale test; step 5, scanning electron microscope; step 6, ABAQUS software modeling; step 7, experimental result analysis;
[0006] In the above step 1, the raw soil is crushed, dried, sieved and then the test soil sample is prepared;
[0007] In the above step 2, the sample is placed in a shear box of a direct shear test machine for a direct shear test;
[0008] In the above step 3, the sample is gently placed on a metal wire mesh, and the sample and the wire mesh are completely immersed in a transparent beaker filled with deionized water to perform a disintegration test;
[0009] In the above step 4, a scaled specimen is prepared and a scaled test is performed;
[0010] In the above step 5, a scanning electron microscope is used to observe the particle morphology and pore characteristics of the soil;
[0011] In the above step 6, according to the actual size and shape of the soil of the Shangcheng ruins, a corresponding two-dimensional trapezoidal geometric model is established in the ABAQUS software, and the material parameters are set according to the data obtained from the step-by-step restoration method test;
[0012] In the above step seven, the test results of direct shear test, disintegration test, scale test and scanning electron microscopy are sorted out to form a complete test data set, and the test results are compared and analyzed to evaluate the effect of the modification treatment.
[0013] As a further technical solution of the present invention, in the step one, the plain soil is crushed, dried, and sieved for later use. The moisture content of the test soil sample is set to 18%, which is higher than the optimal moisture content. Two more soil samples with moisture contents of 20% and 22% are made for the later simulation of the restoration process of the Shang City ruins by ABAQUS software. The direct shear soil sample has a diameter of 61.8 mm and a height of 20 mm, and the disintegration soil sample has a diameter of 39.1 mm and a height of 80 mm. Sodium methyl silicate: water is mixed and stirred in a ratio of 1:99, 3:97, and 5:95, respectively, and then added to the soil sample. After the soil sample is stirred evenly, the soil sample is prepared. There are a total of 15 mix ratios, and 3 soil samples are made in each group as a control group. The sample is placed in a carbonization box, and the test carbonization concentration is set to 1%. The carbonization concentration in the air is about 0.03%, and the carbonization time is set to 0 h, 1 h, 2 h, and 3 h.
[0014] As a further technical solution of the present invention, in step 2, a fully automatic direct shear apparatus is used for the test, the sample is loaded with a vertical pressure of 50 to 200 kPa, increasing by 50 kPa, and the shear rate of the soil sample is set to 0.8 mm / min.
[0015] As a further technical solution of the present invention, in step three, the sample is gently placed on a metal wire mesh, and the sample and the wire mesh are completely immersed in a transparent beaker filled with deionized water. The soil sample is left to stand for 12 hours, and the mass change of the soil sample is recorded every 1 hour.
[0016] As a further technical solution of the present invention, in step 3, the disintegration rate A t As an indicator for evaluating soil collapse characteristics, the calculation formula is:
[0017]
[0018] Where m0 is the original mass of the soil sample, unit (g), m t is the mass of soil sample at time t, unit (g).
[0019] As a further technical solution of the present invention, in the step 4, before the scaled test, a preliminary experiment is carried out, and the penetration depth of the soil sample is studied by using two process methods, spraying and "step-by-step" drip infiltration, and the penetration method of the scaled test is selected preferentially. In the preliminary experiment, the size of the test soil sample is 240mm (length) × 115mm (width) × 53mm (height), and the size of the scaled test sample is a trapezoid with an upper base of 16cm, a lower base of 18cm, a height of 10cm, and a slope foot of 45°. Small squares of 3mm (length) × 2mm (width) are drawn in three layers on the inclined surface of the test block, and the test block is repaired in sections and layers by the "step-by-step" method.
[0020] As a further technical solution of the present invention, in step five, the waste soil after the direct shear test is taken, the soil sample is cut into 1 cm cubes with a steel knife, put into an oven for drying for 8 hours, and the particle morphology and pore characteristics of the soil are observed with a scanning electron microscope at a magnification of 1000 times.
[0021] As a further technical solution of the present invention, in step six, Standard / Explicit is used in ABAQUS to simulate the earthen wall of the Shangcheng ruins, and a two-dimensional trapezoidal geometric model with an upper base of 10m, a lower base of 20m, a height of 10m, and a slope foot of 45° is established. The material parameters are set according to the data obtained from the "step-by-step" repair method test, and the parameters are reduced by the strength reduction method. The specific parameters are as follows: the elastic modulus of the soil is 10MPa, the Poisson's ratio is 0.3, the cohesion C=9.5kPa, the friction angle θ=23.7°, and the soil bulk density is 20kN / m 3 , initial porosity ratio e=1.
[0022] As a further technical solution of the present invention, in step 6, the relationship between the material permeability coefficient and the matrix suction is:
[0023] K w =a w K ws / [a w +(b w ×(u a -u w ))c w ]
[0024] Where: K ws is the permeability coefficient of the saturated soil, which is 5.0×10 -6 m / s(0.018m / h),u a and u w are respectively the air pressure and water pressure in the soil, the slope surface is in contact with the atmosphere, u a Take 0, a w 、b w and c w are material coefficients, which are 1000, 0.01 and 1.7 respectively.
[0025] As a further technical solution of the present invention, in step 6, the relationship between saturation and matrix suction is:
[0026]
[0027] Where: S r is the saturation, S i is the residual saturation, taking 0.08, S n is the maximum saturation, take 1, a s 、b s and c s are material coefficients, taking 1 and 5.0×10 -5 and 3.5.
[0028] Compared with the prior art, the beneficial effects of the present invention are as follows: the present invention improves the ruins soil by adding sodium methyl silicate liquid to repair the ruins, and the sodium methyl silicate reacts with carbon dioxide and water in the air to generate a meshed silicone resin film, which is wrapped on the surface of the soil structure, and can achieve an "inverse capillary effect" to form a hydrophobic layer with excellent performance. The product has micro-expansion, can block pores to increase the density of the soil, improve the strength of the soil, and effectively improve the mechanical properties and water properties of the ruins soil. A step-by-step repair method is adopted to first repair the bottom layer and then repair the upper layer, and finally deepen the material penetration depth, and comprehensively improve the mechanical properties and water properties of the ruins soil. The penetration depth of the sodium methyl silicate waterproofing agent into the soil sample can reach more than 4 cm, and no cracks or collapse occur on the surface of the soil sample, which can increase the penetration depth of the repair material, solve the problem of limited penetration depth of liquid materials, and provide a new idea and method for future earthen ruins repair. BRIEF DESCRIPTION OF THE DRAWINGS
[0029] Figure 1 is a flow chart of the method of the present invention;
[0030] Figure 2 It is a schematic diagram of the step-by-step repair of the present invention;
[0031] Figure 3 It is a size diagram of the test soil sample for the scaled test pre-experiment of the present invention;
[0032] Figure 4 It is a scaled sample diagram of the present invention;
[0033] Figure 5 The shear strength curves of different samples in the embodiment;
[0034] Figure 6 is the shear stress-shear displacement curve of the sample under different normal stresses in the embodiment;
[0035] Figure 7 The disintegration rate curve of soil samples at different carbonization times in the embodiment;
[0036] Figure 8 is the penetration depth curve of the sample in the embodiment;
[0037] Fig. 9 It is the penetration depth curve of the sample at each stage in the embodiment;
[0038] Fig.10 It is a scanning electron microscope image of the sample in the embodiment;
[0039] Fig.11 is the plastic zone of the wall in the embodiment;
[0040] Fig.12 is the slope safety factor in the embodiment;
[0041] Fig.13 It is the displacement contour cloud diagram in the embodiment. DETAILED DESCRIPTION
[0042] The technical solutions in the embodiments of the present invention will be clearly and completely described below in conjunction with the drawings in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, rather than all the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without making creative work are within the scope of protection of the present invention.
[0043] Please see attached Figure 1 -Attached Fig.13 , an embodiment provided by the present invention: a test method for the modified performance of the soil of the Shangcheng ruins under high moisture content:
[0044] The test soil was taken from the wall of Zhengzhou Shangcheng, with a sampling depth of about 1m. According to the classification of soil types in the "Engineering Classification Standard of Soil", the test soil sample was measured to be silty clay, with a liquid limit of 38.7%, a plastic limit of 24.3%, a plasticity index of 14.4, an optimum moisture content of 16.3%, and a maximum dry density of 1.65g / cm 3 ;
[0045] Soil sample preparation: the plain soil was crushed, dried, and sieved for later use. The moisture content of the test soil sample was set to 18%, which was higher than the optimal moisture content. Two more soil samples with moisture contents of 20% and 22% were prepared for the later simulation of the restoration process of the Shangcheng ruins by ABAQUS software. The direct shear soil sample size was 61.8 mm in diameter × 20 mm in height, and the disintegration soil sample size was 39.1 mm in diameter × 80 mm in height. Sodium methyl silicate: water was mixed and stirred in a ratio of 1:99, 3:97, and 5:95, respectively, and then added to the soil sample. The soil sample was stirred evenly before soil sample preparation. There were a total of 15 mix ratios, and 3 soil samples were prepared in each group as a control group. The samples were placed in a carbonization box, and the test carbonization concentration was set to 1%, the carbon dioxide concentration in the air was about 0.03%, and the carbonization time was set to 0 h, 1 h, 2 h, and 3 h. The specific mix ratios are shown in Table 1.
[0046] Table 1 Orthogonal test scheme
[0047]
[0048] Direct shear test: This test uses a fully automatic direct shear apparatus, the sample is loaded with a vertical pressure of 50-200 kPa, and the test is performed in increments of 50 kPa in accordance with the Geotechnical Test Method Standard (GB / T50123-2019), and the soil sample shear rate is set to 0.8 mm / min;
[0049] Disintegration test: Place the sample gently on a metal wire mesh, immerse the sample and the wire mesh completely in a transparent beaker filled with deionized water, let the soil sample stand for 12 hours, and record the mass change of the soil sample every hour. t As an indicator for evaluating soil collapse characteristics, the calculation formula is:
[0050]
[0051] Where m0 is the original mass of the soil sample, unit (g), m t is the mass of soil sample at time t, unit (g);
[0052] Scaled test: Before the scaled test, a preliminary experiment was conducted, using two process methods, spraying and "step-by-step" drip infiltration, to study the penetration depth of soil samples, and the optimal infiltration method for the scaled test was selected. In the preliminary experiment, the test soil sample size was 240mm (length) × 115mm (width) × 53mm (height), and the scaled sample size was a trapezoid with an upper base of 16cm, a lower base of 18cm, and a height of 10cm. The slope foot was 45°. Small squares of 3mm (length) × 2mm (width) were drawn in three layers on the slope of the test block, and the test block was repaired in sections and layers using the "step-by-step" method;
[0053] Scanning electron microscope: Take the waste soil after the direct shear test, cut the soil sample into 1 cm cubes with a steel knife, put it in an oven to dry for 8 hours, and use a scanning electron microscope with a magnification of 1000 times to observe the particle morphology and pore characteristics of the soil;
[0054] ABAQUS software modeling: Standard / Explicit was used in ABAQUS to simulate the earthen wall of the Shangcheng ruins, and a two-dimensional trapezoidal geometric model with an upper base of 10m, a lower base of 20m, a height of 10m, and a slope foot of 45° was established. The material parameters were set according to the data obtained from the "step-by-step" repair method test, and the parameters were reduced using the strength reduction method. The specific parameters are as follows: the elastic modulus of the soil is 10MPa, the Poisson's ratio is 0.3, the cohesion C=9.5kPa, the friction angle θ=23.7°, and the soil bulk density is 20kN / m 3 , the initial porosity ratio e = 1, the relationship between the material permeability coefficient and the matrix suction is:
[0055] K w =a w K ws / [a w +(b w ×(u a -u w ))c w ]
[0056] Where: K ws is the permeability coefficient of the saturated soil, which is 5.0×10 -6 m / s(0.018m / h),u a and u w are respectively the air pressure and water pressure in the soil, the slope surface is in contact with the atmosphere, u a Take 0, a w 、b w and c w is the material coefficient, which is 1000, 0.01 and 1.7 respectively. The relationship between saturation and matrix suction is:
[0057]
[0058] Where: S r is the saturation, S i is the residual saturation, taking 0.08, S n is the maximum saturation, take 1, a s 、b s and c s are material coefficients, taking 1 and 5.0×10 -5 and 3.5;
[0059] Analysis of experimental results: Direct shear test analysis: Soil shear strength is an important indicator for calculating the reliability of earthen site reinforcement. The internal friction angle and cohesion obtained through indoor direct shear test are shown in Table 2. The shear strength of soil samples with different amounts of sodium methyl silicate is significantly higher than that of plain soil, and the internal friction angle and cohesion are improved. After carbonization for 1h, the shear strength and friction angle of soil samples containing 1%, 3%, and 5% sodium methyl silicate are 11kPa, 17.5kPa, 15.5kPa and 6.5 higher than those of plain soil, respectively. °, 6.8°, 6.6°. After carbonization for 2h, the shear strength and friction angle of soil samples containing 1%, 3%, and 5% sodium methyl silicate are 14kPa, 21.5kPa, 20.5kPa and 7.3°, 7.9°, 7.6° higher than those of plain soil, respectively. After carbonization for 3h, the shear strength and friction angle of soil samples containing 1%, 3%, and 5% sodium methyl silicate are 13kPa, 20.5kPa, 16.5kPa and 6.6°, 6.8°, 6.7° higher than those of plain soil, respectively.
[0060] Table 2 Sample direct shear test data
[0061]
[0062]
[0063] As attached Figure 5 As shown in the figure, with the increase of sodium methyl silicate concentration and carbonization time, the shear strength of the soil sample first increases and then decreases. When the amount of sodium methyl silicate is 3%, the shear strength of the soil sample reaches the maximum, which is 21.5kPa, 0.6kPa, and 0.3kPa higher than the plain soil, soil samples containing 1% and 5% sodium methyl silicate, respectively. The shear strength of the soil sample at 2h of carbonization is the largest, which is 5kPa, 4kPa, and 1kPa higher than those at 0h, 1h, and 3h, respectively. Figure 6 The shear stress and shear displacement curves of the sample. Under different normal stresses, the shear stress of the soil sample increases with the increase of strain, but the rate of increase gradually decreases. The curve has no peak value, showing obvious strain hardening characteristics. The shear process is accompanied by the tumbling, crushing and rearrangement of particles, resulting in a not very flat curve. The carbonization of sodium methyl silicate mainly occurs on the surface of the soil sample. The carbonization reaction consumes water. The polymethylsiloxane generated by it has a water-retaining effect to a certain extent, which can slow down the loss of water in the soil sample. Sodium methyl silicate has a micro-expansion effect. A large amount of flocs generated will expand inside the soil sample. Excessive expansion will cause cracks inside the soil sample, which will affect the shear strength of the soil sample. This results in the shear strength of the soil sample containing 5% sodium methyl silicate and carbonized for 3h being not as good as the soil sample containing 3% sodium methyl silicate and carbonized for 2h.
[0064] Disintegration test analysis: The disintegration morphology is a direct representation of the disintegration process of the soil sample. The whole disintegration process of the soil sample is recorded with a camera, as shown in the attached video. Figure 7As shown in the figure, the disintegration curves of soil samples with different mix ratios all show a state that the slope is first large, then small, and finally tends to be gentle. The initial disintegration rate of the soil sample is large, and it is in a violent disintegration state and then gradually decreases. Finally, the disintegration rate remains basically unchanged, and enters a stable disintegration process until the soil sample is completely disintegrated. The plain soil A00 falls off quickly after entering the water, and the disintegration rate reaches the maximum in the first hour. The soil sample completely disintegrates within 2 hours, and the soil sample has poor disintegration resistance. The soil samples with other mix ratios have low waterproofing agent concentrations or insufficient carbonization time, and no sufficient polysiloxane film is generated. After 12 hours, the soil samples all disintegrate. The soil samples A53, A32 and A33 with outstanding disintegration resistance have been absorbing water and swelling in the first 5 hours, 8 hours and 11 hours respectively. The water absorption of the soil samples is greater than the disintegration amount. The curve shows that the disintegration rate is negative growth, and the disintegration rate exceeds the critical point of water absorption at 6 hours, 9 hours and 11 hours respectively. The amount of soil sample disintegration is greater than the amount of water absorption. After 12 hours of violent disintegration of soil sample A53, 43% of residual soil remains. After 12 hours of a small amount of cracks appearing in A32, 50% of residual soil remains. A33 has a small amount of soil falling off or even no soil. When the amount of sodium methyl silicate added is the same, with the increase of carbonization time, the soil sample's disintegration resistance becomes better and better. The soil sample carbonized for 3 hours has the best disintegration resistance, and the residual mass is 0.78g, 0.72g, and 0.18g more than that of carbonized for 0h, 1h, and 2h, respectively. When the carbonization time is the same, with the increase of sodium methyl silicate addition, the soil sample's disintegration resistance increases first and then decreases. The soil sample containing 3% sodium methyl silicate has the best disintegration resistance, and the residual mass is 0.78g, 0.35g, and 0.43g more than that of plain soil, 1%, and 5% sodium methyl silicate, respectively. Sodium methyl silicate will decompose into methyl silicic acid when it meets water and carbon dioxide, generating water-resistant polymethylsiloxane. Its chemical reaction is as follows:
[0065] 2CH3Si(OH)2ONa+CO2+H2O→2CH3Si(OH)3+Na2CO3
[0066] nCH3Si(OH)3→(CH3SiO 3 / 2 ) n +3 / 2H2O
[0067] Its molecular structure contains silanol (Si—OH) and silyl (Si—CH3), and the generated polysiloxane film has -CH3 molecules. At the same time, -CH3 is arranged on the outer surface of the film formed by Si-O bond connection. The hydrophobic film is firmly adsorbed on the surface of the soil sample, thereby changing the path of water migration and inhibiting the erosion of the soil sample by water. Therefore, the soil sample mixed with sodium methyl silicate has a long disintegration time and has good disintegration resistance. At the same time, the carbonization reaction will promote the formation of related chemical and mineral components in the soil modified by sodium methyl silicate, and the density of the soil sample after carbonization is increased, and the water resistance is better;
[0068] Scaled test analysis: In order to compare the penetration depth of soil samples in two different treatment methods, the soil samples treated in two different ways were slowly inserted into the adobe with a tie wire at the same time, and the penetration depth of the soil samples was measured with a steel ruler. Figure 8 The penetration depth curves of soil samples of the "step-by-step" drip infiltration method and the spraying method are shown in Figure 2. The spraying method stops infiltration after about 40 minutes, and the penetration depth is limited, with a maximum penetration depth of 2.1 cm. After the "step-by-step" drip infiltration method lasts for about 4.6 hours, all the soil samples are penetrated, and the penetration depth is 5.3 cm, which is 2.5 times that of the spraying method. Since the spraying method requires intermittent time, it is difficult to always have sufficient reinforcement on the surface of the soil sample to maintain penetration, and the reinforcement reacts with the contact air to form a waterproof film, shortening the infiltration time. The penetration time is too long, which is not conducive to the penetration of subsequent waterproofing agents. However, the "step-by-step" drip infiltration method does not have this problem, because the geotextile used in the drip infiltration method contains sufficient reinforcement agents, which can keep the soil surface moist and reduce the surface conjunctiva caused by evaporation, effectively prolonging and deepening the penetration time and penetration depth of the waterproofing agent, solving the problem of shallow soil penetration depth. According to the comparison of the two methods in the preliminary experiment, it is found that the soil penetration depth of the "step-by-step" drip infiltration method is deeper, so the "step-by-step" drip infiltration method is used in the scaled test, as shown in the attached figure. Fig. 9 As shown in the figure, with the increase of the dosage of sodium methyl silicate and the growth of time, the penetration depth of the soil sample gradually increases. The penetration depth of the first stage of repair is 2-3mm deeper than that of the second and third stages, and the penetration depth of the second stage of repair is 2mm deeper than that of the third stage. The penetration range of the waterproofing agent spreads in an arc shape, and a thin waterproof film is formed around it, which hinders the penetration of the waterproofing agent in the latter stage, resulting in the penetration depth of the latter stage being slightly shallower than that of the previous stage. The sample is divided into three stages of penetration: bottom, middle and upper. In each stage, the soil sample can almost penetrate through and there will be no cracks or collapse on the surface of the soil sample. At the same time, the geotextile is light in weight, good in permeability, strong in water retention and storage capacity, and can maintain sufficient strength and elongation under dry and wet conditions. The penetration depth of the soil sample can reach more than 4cm, which verifies the feasibility of the "step-by-step" repair method.
[0069] Microscopic electron microscope analysis: attached Fig.10The electron microscope images of soil samples with different proportions show that the internal cracks of the plain soil A00 are deep and long, showing irregular strip distribution, the soil particles are unevenly arranged, the structure is loose, the bonding effect between the particles is relatively weak, and there is basically no filler in the pores. The internal pores and cracks of the soil sample A11 containing 1% sodium methyl silicate and carbonized for 1h are reduced, the amount of sodium methyl silicate added is small, and a complete film is not formed. Only a small amount of flocs fill the pores, and the soil strength is not significantly improved. The soil sample A32 containing 3% sodium methyl silicate and carbonized for 2h has a layer of The soil particles are arranged more closely, and there are basically no suspended soil particles. The soil skeleton has good integrity. Sodium methyl silicate has formed a complete film in the soil, wrapping the soil particles. The macroscopic performance is that the soil strength is greatly improved. There are a lot of polymethylsiloxane floccules on the surface of soil sample A53 containing 5% sodium methyl silicate and carbonized for 3h, but there are shallow microcracks. The excessive dosage of sodium methyl silicate causes a great change in the soil structure and inhibits the formation of normal crystal forms. The macroscopic performance is that the soil strength is reduced.
[0070] Stability analysis of repaired city walls: At present, the stability analysis of earthen sites is mainly based on the elastic-plastic theory of rock and soil, and the constitutive relationship of soil is considered for analysis. When simulating the stability of earthen sites, the weakening effect of adverse conditions such as wind and rain erosion on the physical and mechanical properties of the site soil should be considered. The strength reduction factor Fr is used to evaluate the stability of the soil. The corresponding value when Fr is unstable is the stability safety factor of the model soil. According to the "Technical Code for Building Slope Engineering" (GB50330-2013), when the safety factor Fs of the slope is less than 1.0, the slope is in an unstable state. At this time, the slope is very easy to become unstable. The indoor test results obtained the performance parameters of the improved soil with different curing times. Taking the plain soil A00 and A32 as representatives, the reduced parameters were substituted into the model in the ABAQUS software for calculation to obtain the safety stability coefficient under the corresponding parameters, as shown in Table 3.
[0071] Table 3 Reduction coefficient
[0072]
[0073] As attached Fig.11 As shown in the figure, during the repair process, the plastic zone of the slope of the Shangcheng city wall became larger. When the increment step t = 3.898, the slope foot showed yield. When the increment step t = 4.580, the plastic zone was completely connected. After the repair with sodium methyl silicate, the plastic zone was significantly reduced, and the stability of the city wall was significantly improved. Fig.12 The horizontal axis represents the safety factor of the slope, and the vertical axis represents the vertical displacement of the slope. During the restoration process, the safety factor Fs1 of the Shangcheng wall was 1.12, and the safety factor Fs2 after modification with sodium methyl silicate was 1.92, which proves the feasibility of the "step-by-step" earthen ruins restoration method. Fig.13 As shown in (a), as the plastic zone continues to expand, the slope forms an arc-shaped sliding surface extending from the bottom to the top. Fig.13 (a) and 13(b), it can be seen that the slope displacement deformation was relatively large before the repair, and the slope displacement was significantly reduced after the repair, and no obvious slope sliding surface appeared. In summary, sodium methyl silicate can improve the shear strength of the Shangcheng wall and effectively reduce the vertical displacement of the wall. The simulation results are basically consistent with the experimental results.
[0074] Based on the above, the advantages of the present invention are: sodium methyl silicate has excellent hydrophobicity, weather resistance and durability. This paper takes the Shang City ruins as the research object, adds sodium methyl silicate liquid to improve the ruins soil, and the carbonized sodium methyl silicate can effectively improve the mechanical properties and water properties of the ruins soil. As the concentration of sodium methyl silicate and the carbonization time increase, the shear strength and internal friction angle of the soil sample first increase and then decrease. The shear strength and internal friction angle of the soil sample containing 3% sodium methyl silicate and carbonized for 2h are the largest. As the concentration of sodium methyl silicate increases, the disintegration resistance of the soil sample first increases and then decreases. The soil sample containing 3% sodium methyl silicate has the best disintegration resistance. As the carbonization time increases, the disintegration resistance of the soil sample becomes better and better. The soil sample carbonized for 3h has the best disintegration resistance. Using the "step-by-step progressive" method, sodium methyl silicate waterproofing agent The penetration depth of soil samples can reach more than 4cm, and there are no cracks or collapse on the surface of the soil samples. The penetration depth of the repair material can be improved and the problem of limited penetration depth of liquid materials can be solved. Scanning electron microscope observation found that the contact between the particles of the soil samples doped with sodium methyl silicate was mainly face-to-face contact, the number and depth of pores were significantly reduced, and flocs on the surface of the soil particles strengthened the connection between the soil particles. The soil sample containing 3% sodium methyl silicate and carbonized for 2h had the best density. ABAQUS was used to conduct a stability analysis of the wall of Zhengzhou Shang City. The safety factor of the repair of the wall of Shang City under high moisture content was 1.12, and the safety factor after modification with sodium methyl silicate was increased to 1.9, which proved the feasibility of the "step-by-step" earthen site restoration method and provided a new method for site restoration.
[0075] It will be apparent to those skilled in the art that the invention is not limited to the details of the exemplary embodiments described above and that the invention can be implemented in other specific forms without departing from the spirit or essential features of the invention. Therefore, the embodiments should be considered exemplary and non-limiting in all respects, and the scope of the invention is defined by the appended claims rather than the foregoing description, and it is intended that all variations falling within the meaning and scope of the equivalent elements of the claims be included in the invention. Any reference numeral in a claim should not be considered as limiting the claim to which it relates.
Claims
1. The test method for the modified performance of the Shangcheng ruins soil under high water content comprises the following steps:
1. soil sample preparation; 2. direct shear test; 3. disintegration test; 4. scale test; 5. scanning electron microscope; 6. ABAQUS software modeling; 7. experimental result analysis; the method is characterized in that: In the above step 1, the raw soil is crushed, dried, sieved and then the test soil sample is prepared; In the above step 2, the sample is placed in a shear box of a direct shear test machine for a direct shear test; In the above step 3, the sample is gently placed on a metal wire mesh, and the sample and the wire mesh are completely immersed in a transparent beaker filled with deionized water to perform a disintegration test; In the above step 4, a scaled specimen is prepared and a scaled test is performed; In the above step 5, a scanning electron microscope is used to observe the particle morphology and pore characteristics of the soil; In the above step 6, according to the actual size and shape of the soil of the Shangcheng ruins, a corresponding two-dimensional trapezoidal geometric model is established in the ABAQUS software, and the material parameters are set according to the data obtained from the step-by-step restoration method test; In the above step seven, the test results of direct shear test, disintegration test, scale test and scanning electron microscopy are sorted out to form a complete test data set, and the test results are compared and analyzed to evaluate the effect of the modification treatment.
2. The test method for the soil modification performance of Shangcheng ruins under high water content according to claim 1 is characterized by: In the step 1, the plain soil is crushed, dried, and sieved for later use. The moisture content of the test soil sample is set to 18%, which is higher than the optimal moisture content. Two more soil samples with moisture contents of 20% and 22% are prepared for the later simulation of the restoration process of the Shangcheng ruins by ABAQUS software. The direct shear soil sample has a diameter of 61.8 mm and a height of 20 mm, and the disintegration soil sample has a diameter of 39.1 mm and a height of 80 mm. Sodium methyl silicate: water is mixed and stirred in a ratio of 1:99, 3:97, and 5:95, respectively, and then added to the soil sample. After the soil sample is evenly stirred, the soil sample is prepared. There are a total of 15 mix ratios, and 3 soil samples are prepared in each group as a control group. The sample is placed in a carbonization box, and the test carbonization concentration is set to 1%, the carbon dioxide concentration in the air is about 0.03%, and the carbonization time is set to 0 h, 1 h, 2 h, and 3 h.
3. The test method for the soil modification performance of Shangcheng ruins under high water content according to claim 1 is characterized in that: In the step 2, a fully automatic direct shear apparatus is used for the test, the vertical pressure of the sample loading is 50 to 200 kPa, increasing by 50 kPa, and the shear rate of the soil sample is set to 0.8 mm / min.
4. The test method for the soil modification performance of Shangcheng ruins under high water content according to claim 1 is characterized in that: In the step three, the sample is gently placed on a metal wire mesh, and the sample and the wire mesh are completely immersed in a transparent beaker filled with deionized water. The soil sample is left to stand for 12 hours, and the mass change of the soil sample is recorded every 1 hour.
5. The test method for the soil modification performance of Shangcheng ruins under high water content according to claim 4 is characterized in that: In the step 3, the disintegration rate A t As an indicator for evaluating soil collapse characteristics, the calculation formula is: Where m0 is the original mass of the soil sample, unit (g), m t is the mass of soil sample at time t, unit (g).
6. The test method for the modification performance of the soil of the Shang City ruins under high water content according to claim 1 is characterized in that: In the step 4, before the scaled test, a preliminary experiment is carried out, and the penetration depth of the soil sample is studied by using two process methods, spraying and "step-by-step" drip infiltration, and the penetration method of the scaled test is selected preferentially. In the preliminary experiment, the size of the test soil sample is 240 mm (length) × 115 mm (width) × 53 mm (height), and the size of the scaled test sample is a trapezoid with an upper base of 16 cm, a lower base of 18 cm, a height of 10 cm, and a slope foot of 45°. Small squares of 3 mm (length) × 2 mm (width) are drawn in three layers on the inclined surface of the test block, and the test block is repaired in sections and layers by the "step-by-step" method.
7. The test method for the modification performance of the Shangcheng ruins soil under high water content according to claim 1 is characterized by: In the step 5, waste soil after the direct shear test is taken, and the soil sample is cut into 1 cm cubes with a steel knife, placed in an oven for drying for 8 hours, and the particle morphology and pore characteristics of the soil are observed with a scanning electron microscope at a magnification of 1000 times.
8. The test method for the soil modification performance of Shangcheng ruins under high water content according to claim 1 is characterized by: In step 6, Standard / Explicit is used in ABAQUS to simulate the earthen wall of the Shangcheng ruins, and a two-dimensional trapezoidal geometric model with an upper base of 10m, a lower base of 20m, a height of 10m, and a slope foot of 45° is established. The material parameters are set according to the data obtained from the "step-by-step" repair method test, and the parameters are reduced by the strength reduction method. The specific parameters are as follows: the elastic modulus of the soil is 10MPa, the Poisson's ratio is 0.3, the cohesion C=9.5kPa, the friction angle θ=23.7°, and the soil bulk density is 20kN / m 3 , initial porosity ratio e=1.
9. The test method for the modification performance of the soil of the Shang City ruins under high water content according to claim 8 is characterized in that: In step 6, the relationship between the material permeability coefficient and the matrix suction is: K w =a w K ws / [a w +(b w ×(u a -u w ))c w ] Where: K ws is the permeability coefficient of the saturated soil, which is 5.0×10 -6 m / s(0.018m / h),u a and u w are respectively the air pressure and water pressure in the soil, the slope surface is in contact with the atmosphere, u a Take 0, a w 、b w and c w are material coefficients, which are 1000, 0.01 and 1.7 respectively.
10. The test method for the modification performance of the soil of Shangcheng ruins under high water content according to claim 8, characterized in that: In step 6, the relationship between saturation and matrix suction is: Where: S r is the saturation, S i is the residual saturation, taking 0.08, S n is the maximum saturation, take 1, a s 、b s and c s are material coefficients, taking 1 and 5.0×10 -5 and 3.5.
Citation Information
Patent Citations
Earthen archaeological site micro-shrinkage crack grouting material and preparation method and application thereof
CN112500035A
Tailing dam infiltration line analysis method
CN118094991A
Mixing design method for improved soil
JP2005273387A
Method for repairing wall diseases of earthen architecture
US20230417074A1
Cited By
Reinforcing material for earthen archaeological site protection and preparation method thereof
CN119841583A